Podmiotowość w pedagogice chrześcijańskiej o inspiracji tomistycznej - Jarosław Horowski (Nicolaus Copernicus University in Toruń, 2009)
The theme of being a subject is one of the most important themes in contemporary pedagogical discussions. There is a problem appearing in these discussions connected with understanding the term 'being a subject'. Some philosophers and theorists of education maintain that each human being is a subject. Others indicate that people become the subjects in a process of individual development, in consequence of development of the rationality and the freedom. In the article the author tries to explain how Thomistic philosophy and pedagogy understand 'being a subject'. He indicates that it is necessary to differentiate being a subject in the metaphysical sense (in this sense each human being is a subject) from being a subject in the functional sense (in this sense a human being can become a subject). A lot of problems result from using one word to describe two different subjects. The author indicates also the Thomistic theory of moral habits as the theory which refers to the theme of 'being a subject' in the functional sense and discuses the Thomistic theory of knowledge in the context of the thesis of poststructuralism that it is impossible to become a subject because the human mind is violated by different concepts of the world and in consequence of this fact the human being is unable to autonomous activity. Referring to the thinking of the Thomistic philosophers and theorists of education the author argues that education based on experience of the truth and the goodness of the reality, which isn't connected with any ideology, make it possible to help young people to become the subjects.